The relationship between emotional intelligence ability and teacher efficacy - Valente, Sabina (2020)
Emotional intelligence and self-efficacy are considered two of the most fundamental teachers’ characteristics to create positive effects on students. Recent research on teacher efficacy has turned from a focus on mastery of content area and lesson plan development to the identification of teacher beliefs and the emotional self-regulation required for teaching and student learning. The purpose of this research was examined whether emotional intelligence abilities influence teacher efficacy. The relationship between teacher gender, length of teaching experience and academic formation with emotional intelligence abilities is also analyzed. The sample comprised 634 Portuguese school teachers. Data sources included the Emotional Skills and Competence Questionnaire for Teachers, and the Teacher Efficacy in Classroom Management and Discipline Scale. The findings, using structural equation modeling, showed that school teachers with greater skills at perceiving, understanding, expressing, classifying, managing and regulating emotions demonstrated greater levels of teacher efficacy. Therefore teachers’ emotional intelligence abilities positively influence teacher efficacy. Having teachers who are apt to perceive and manage emotions will be salutary for the personal development of students, as well as for structuring a positive and self-regulating learning environment. So the results support the teachers’ emotional intelligence ability to job performance, and add to literature suggesting that to succeed in the complex and demanding school setting, teachers must develop the necessary emotional skills for enhancing their efficacy. This research contributes to the importance of being created in the teachers’ academic training, the emotional education discipline.